2018
DOI: 10.1037/ccp0000322
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing with personalized feedback to reduce alcohol use in HIV-infected men who have sex with men: A randomized controlled trial.

Abstract: In MSM living with HIV, MI shows substantial promise for reducing heavy drinking and for reducing condomless sex among those at risk. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
64
1
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 54 publications
(69 reference statements)
2
64
1
4
Order By: Relevance
“…Game Plan participants also reported significantly fewer alcohol-related problems than controls, and these differences appeared stronger in the later months of the follow-up period. This pattern of results is consistent with some other studies testing of brief alcohol interventions among MSM, which show that the effects of these interventions on drinking outcomes may strengthen over time (34). Contrary to our hypotheses, however, Game Plan participants did not consume fewer drinks when they drank than controls.…”
Section: Discussionsupporting
confidence: 91%
“…Game Plan participants also reported significantly fewer alcohol-related problems than controls, and these differences appeared stronger in the later months of the follow-up period. This pattern of results is consistent with some other studies testing of brief alcohol interventions among MSM, which show that the effects of these interventions on drinking outcomes may strengthen over time (34). Contrary to our hypotheses, however, Game Plan participants did not consume fewer drinks when they drank than controls.…”
Section: Discussionsupporting
confidence: 91%
“…Based on a systematic review of the literature and meta-analysis, Scott-Sheldon and colleagues reported in 2017 that there were only 21 studies that reported on individual-level interventions designed to address alcohol use among PWH, 71% of which were clinic-based [17]. Consistent with our approach, studies that targeted alcohol alone (vs. multiple HIV-related behaviors) and that were clinic-based (vs. recruiting from other/mixed settings), were found to be more successful at decreasing alcohol use [14][15][16][17], though these effects may vary based on baseline level of motivation and intervention strategy [13]. Building on this literature and our experiences evaluating ISAT among PWH with higher and lower levels of alcohol use [21,22], the current study provides additional support for approaches that include MI-based interventions that target alcohol use in clinic-based settings to promote alcohol reduction among PWH.…”
Section: Discussionsupporting
confidence: 58%
“…Despite its potential to improve individual and public health, brief intervention with subsequent indicated treatment is inconsistently delivered to PWH [11], and, to date, only a limited number of studies have been specifically designed to address unhealthy alcohol use (defined as the spectrum of alcohol use including at-risk drinking and alcohol use disorder) among PWH [12][13][14][15][16][17]. These studies have generally focused on evaluation of a specific medication (i.e., naltrexone) [12] or behavioral intervention [13][14][15][16] and some focused on a specific patient population (e.g., women, men who have sex with men). None of these studies offered a comprehensive package that allowed evaluation of initial patient response to a lower intensity intervention prior to adding additional services.…”
mentioning
confidence: 99%
“…We used a cluster-randomized, type 2 hybrid trial to simultaneously test the impact of the ISF strategy (as an adjunct to the ATTC strategy) on: (1) the integration of a MIBI for SUDs within HIV-CBOs across the United States, and (2) the effectiveness of the MIBI (as an adjunct to UC within HIV-CBOs). Contributing to the growing literature on the effectiveness of facilitation-based strategies (74)(75)(76)(77)(78)(79)(80)(81)(82) and the effectiveness of MIBIs for SUD within HIV service settings (18,(83)(84)(85)(86)(87)(88), we found at least two findings of significance. First, we found evidence that the ISF strategy had a significant impact on improving the integration of the MIBI for SUDs, at least in terms of significantly improving the consistency and quality of MIBI implementation during the implementation phase (i.e., implementation effectiveness).…”
Section: Discussionmentioning
confidence: 69%